Complete Fundus Mobilization Reduces Dysphagia After Nissen Procedure. (June 2021) - Renzi, Adolfo; Di Sarno, Giandomenico; d'Aniello, Francesco; Brillantino, Antonio; Minieri, Gianluca; Coretti, Guido; Barbato, Domenico; Barone, Gianni
Background. Anti-reflux surgery is an effective treatment for gastroesophageal reflux disease (GERD). Nevertheless, surgery is still indicated with great caution in relation to the risk of complications, and in particular to postoperative dysphagia (PD). Objective. To compare the clinical outcomes, with particular focus on the incidence and severity of PD, of laparoscopic Nissen–Rossetti fundoplication (NRF) and floppy Nissen fundoplication (FNF) with complete fundus mobilization, in the surgical treatment of GERD. Methods. Ninety patients with GERD were enrolled. Forty-four patients (21[47.7%] men, 23[52.2%] women; mean age 42.4 ± 14.3 years) underwent NRF (Group A), and 46 patients (23[50%] men, 23[50%] women; mean age 43.3 ± 15.4 years) received laparoscopic FNF with complete fundus mobilization (Group B). Clinical assessment was performed using a structured questionnaire and SF-36 quality of life (QoL) score. PD was assessed using a validated classification, and an overall outcome was also determined by asking the patient to score it. Results. At 24-month follow-up, 38 (88.3%) patients in Group A vs 39 (86.6%) in Group B reported to be completely satisfied with reflux relief and free of protonic pump inhibitors (PPIs), while 3 (6.9%) in Group A vs 2(4.4%) in Group B reported occasional PPI intake and 2(4.6%) in Group A vs 4(8.8%) in Group B needed regular PPI use. Persistent PD was observed in 8(18.6%) patients in Group A and in 2(4.4%) in Group B ( P = .03). No significant differences were found in the QoL score and in the overall outcome perceived by the patients. Conclusion. FNF, with complete fundus mobilization, appears to be associated with a lower rate of postoperative persistent dysphagia.